The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5603/gp.2020.0029
|View full text |Cite
|
Sign up to set email alerts
|

Application of prenatal ultrasonography and magnetic resonance imaging on fetal agenesis of corpus callosum

Abstract: Objectives: To evaluate the diagnostic value and clinical application of prenatal ultrasonography (US) and Magnetic Resonance Imaging (MRI) for different types of fetal Agenesis of the Corpus Callosum (ACC). Material and methods: There were 42 cases of fetal ACC discovered by routine US, including complete ACC 18 cases and partial ACC 24 cases, checked by MRI within 1 week. The results were confirmed by head ultrasound after birth or brain biopsy after labor induction. Results: From prenatal ultrasonic diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Findings within many studies demonstrated discrepancies between the prenatal and postnatal or post-mortem diagnoses (Bell et al, 2015;Craven, Bradburn, & Griffiths, 2015;Griffiths et al, 2017;Huras et al, 2017;Jarre et al, 2017;Min, A & Zou, L., 2020;Santirocco et al, 2019). This discrepancy may relate to the technology, method of diagnosis, or the experience of the diagnostician (Cignini et al, 2010).…”
Section: The Prenatal Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Findings within many studies demonstrated discrepancies between the prenatal and postnatal or post-mortem diagnoses (Bell et al, 2015;Craven, Bradburn, & Griffiths, 2015;Griffiths et al, 2017;Huras et al, 2017;Jarre et al, 2017;Min, A & Zou, L., 2020;Santirocco et al, 2019). This discrepancy may relate to the technology, method of diagnosis, or the experience of the diagnostician (Cignini et al, 2010).…”
Section: The Prenatal Diagnosismentioning
confidence: 99%
“…Griffiths et al (2017) reported that termination was offered to 21 parents based upon the ultrasound results alone and that this option was retracted in five cases after fetal MRI (fMRI) refuted the ACC diagnosis. The false-positive diagnosis of ACC by ultrasound was described in three studies where fMRI ruled out the anomaly in 1/11 (Huras et al, 2017), 28/78 (Jarre et al, 2017) and 15/42 (Min, et al 2020). A further ultrasound accuracy study that utilized post-mortem, fMRI, and postnatal imaging as references, found that 54 post-ACC SCOPING REVIEW 12 mortems confirmed ACC within 46 fetuses, two fetuses had a typically developed CC, and the final six were inconclusive (Santirocco et al, 2019).…”
Section: The Prenatal Diagnosismentioning
confidence: 99%
See 1 more Smart Citation